Posted by **Anonymous** on Tuesday, August 20, 2013 at 9:50am.

if y=(x +3)2, then (-2x-6)2 must equal which of the following:

a) -4y2

b) -2y2

c) -4y

d) 4y

## Answer This Question

## Related Questions

- Algerbra - f y = (x + 3)2, then (-2x - 6)2 must equal which of the following? A...
- maths - Solve the system. 3x2 - 2y2 = -5 x2 + y2 = 25 A. (3, 4), (3, -4), (-3, 4...
- arithmetic - How do I solve these questions? 3 1/3 - 2 2/5= 2.75 + .003 + .158...
- math,finite mathematics - this is what i have so far for the following problem ...
- school work - Factor the following polynomials 9-x^2 4x^2+81-36 4y2^+16y+16 x2^-...
- maths - 2. The tangent to the curve y = ex2 drawn at the point (e, ee) ...
- mathematics - Consider the following eqution x2 + 4y2 + 9z2 = 14x + 28y+42z + ...
- maths - The real numbers x and y satisfy the nonlinear system of equations {2x2...
- Math - Which of the following is one of the factors of 2y2 - 6y - 20 Is the ...
- Math - a/b + b/a = x a/b - b/a = y in the equation above, if a is (not equal) to...

More Related Questions